Perbedaan Penyuluhan Dengan Media Flip Chart Dan Booklet Terhadap Keterampilan Menggosok Gigi. - sardi; Astu Rahman, Waljuni; K. Utami, Naning; Fansurna, Anderi (Poltekkes Kemenkes Banjarmasin, 2022)
Based on the results of a preliminary study conducted at SDN 1 Samba Kahayan in March 2023, through dental and oral examinations, 10 students showed that dental and oral hygiene (OHI-S) was 60% in the moderate category, 40% in the poor category, and 100% dental caries. . This research aims to determine the difference between counseling using Flip Chart and Booklet media on tooth brushing skills for students at SDN 1 Samba Kahayan. The type of research used is quasi-experimental research (quasi experiment) and the research design is